The Role Of Competitive Culture In The History Of Uzbek National-Spiritual Development - Shavkat o’g’li, Shakarov Jasurbek; Tadqiqotchi, Mustaqil (Pubmedia Social Sciences and Humanities, 2024)
The Uzbek people are considered one of the peoples with a huge national-spiritual culture. The development of our national-spiritual culture dates back to very ancient times, and their historical manifestations are manifested in our ancient myths and legends, fairy tales, sources of religious thought, national traditions and rituals, traditions and folk games.